Primum non nocere (First, do no harm). Issue 6 (2nd December 2020) - Ibrahim, Maria
Abstract : Maria Ibrahim, a kidney doctor in training, explains the vital role of statistics and statistical analysis in transplant medicine: from matching donor organs to patients, to helping doctors and patients discuss the risks and benefits of a life‐changing operation Abstract : Maria Ibrahim, a kidney doctor in training, explains the vital role of statistics and statistical analysis in transplant medicine: from matching donor organs to patients, to helping doctors and patients discuss the risks and benefits of a life‐changing operation.